(3JMjI Cgd GdbHhQ HGdeCKhQs - (3GdYGedj GdCUagGfj GdcGXej, CHh eMeO, MSf Hf gGOj Hf eMeO Ydj, J (B1354(3g`s ((3GdfLa GdCTQas)
(3ChdgG (B:s
(3GdMeO ddg (B...(3aj GdETGQI Edi ehGVY bHhQ LeGYI ef ChdGO GdCFeI (B.. (3hLeGYI ef bHhQ GdYdeGA GdCLdGA GdPjf jSJMH RjGQJge hfPcQ Pdc aj aUdjf (B...s
(3BNQgG (B:s
... (3hGdPj jYQa HGdMdI HbHQ GdSjO Ydj Hf WGhhS aj GdHSJGf gh bHQ GHfg GdSjO Ydj GdePchQ aEfg jSJQc eYg aj GdGSe hGddbH hdG eLGd dCcKQ ef gPG hGdMeO ddgs
(3efShNI Yf fSNI efShNI Yf fSNI efShNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/224s
(3GdPQjYI (B3 - 267( 1814 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs